The ownership of funds and systems for reparation of very large accidents - Kristian Bolin (Lund University, School of Economics and Management, Department of Economics, 1999)
The present system for reparation of very large oil accidents at sea neither gives incentives to take efficient care, nor allow for compensation of all damages. The reason is that the magnitudes of the accidents that we study are so big that the total assets of the injurer are not sufficient to pay for all damages. That is, strict liability for the injurer does not supply incentives enough for the liable party to take efficient care. In order to ensure that victims are compensated, in case of an accident, mandatory liability insurance has been introduced. This may have eroded the incentives to take care even further because of the moral hazard problem. Another component of the compensation system is the 1969 Brussels International Convention on Civil Liability for Oil pollution damage, CLC. The purpose of this convention is to improve the situation with the apparent inadequacy of the system to meet the compensation demands from victims. The CLC forces the states which have complied to establish a fund which has the purpose of compensate victims of an oil accident. However, the compensation coming from the fund does not have any effect on the injurer's incentives to take care. Since the amount paid from the fund in reparation will not affect the injurer's profit, there is no link induced between the level of care and the fund. A construction that would create a link between the injurer's welfare and the assets of the fund is to let the injurer own the fund, and hence earn the interest from the funded means, but place strict and unlimited liability on the fund.
Keywords: K13; K32; 330; Liability; Reparation; Compensation